The Classwide Peer Tutoring as a Bridge to Social Inclusion: Teachers’ Perspectives from an Inclusive Classroom - Puspita Maharani; Maslathif Dwi Purnomo (Universitas Islam Negeri Palopo, 2026)
Classwide Peer Tutoring (CWPT) has been recognized as an effective instructional strategy, yet its socio-emotional impacts within inclusive English as Foreign Language (EFL) classrooms remain under-explored. While contemporary Indonesian EFL research heavily focuses on digital innovations, this study addresses an empirical gap by investigating a nondigital, peer-mediated approach within local inclusive primary education. Utilizing Interpretative Phenomenological Analysis (IPA), this study explores how a classroom teacher and a shadow teacher interpret their lived experiences in implementing CWPT to foster social inclusion for a first-grade student with an Autism-Dysgraphia profile. Data were collected through semi-structured interviews and field observations over a full program cycle. The analysis revealed five interconnected experiential themes: (1) focusing on independence before academics; (2) stepping back to let the student stand alone; (3) using friends as social bridges; (4) moving from writing to speaking in English; and (5) moving from feeling overwhelmed to professional pride. The findings demonstrate that CWPT operates not merely as an academic tool, but as a critical scaffolding mechanism that fosters collective empathy. Crucially, student progress is not an isolated outcome of CWPT, but is significantly accelerated by natural developmental maturation and a tri-partite communication loop involving parents. Practically, these insights offer valuable guidance for teachers regarding instructional adaptations and highlight the boundary conditions of transferring peer-mediated frameworks into high-density classrooms without secondary teacher support.